The effect of an exchange rate devaluation on a small open economy with an external debt overhang - Yap, Josef T. (1990)
One reason a developing country with a relatively open economy would be hesitant to devalue its currency is the effect of the change in the official exchange rate on the government budget items related to the external debt overhang. It is shown that in an economy characterized by mark-up pricing behavior, a currency devaluation would be stagflationary if a particular condition is satisfied. The latter relates the movement of the peso-equivalent interest payments on external debt to the exchange rate response of the trade balance. Assuming a devaluation is necessary to correct for distortions in the economy, one can conclude that potential short-term contractionary effects may be avoided if meaningful debt forgiveness will accompany the adjustment in the exchange rate.
Includes bibliographical references (page 47).
Keywords: Devaluation of currency; External debts; Public debts -- Philippines